Quantification of land use threats to a flagship species and its meadow habitats within urban landscape - K. Krzosek; P. Nowicki (The European Zoological Journal)
In recent decades insects have experienced severe declines worldwide, and the main threats to their populations include the loss, fragmentation and deterioration of their habitats, due to land use changes such as urbanisation, afforestation, and natural succession. While the impacts of such threats have been the subject of numerous investigations, there is a lack of studies that analyse them jointly, and assess their relative importance, especially in urban and peri-urban landscapes. Based on extensive monitoring data (spanning the period 2003–2022), we evaluated negative effects of expansion of built-up areas, afforestation of meadows, and succession due to meadow abandonment on habitat availability and quality as well as local population dynamics of a flagship butterfly Phengaris alcon in an urban landscape. Direct urbanisation pressure had the least impact on the metapopulation decrease in absolute terms, because it only affected poor-quality meadow fragments. In contrast, afforestation targeted relatively well-preserved meadows, and was responsible for substantial habitat loss and was the predominant reason for the decline in butterfly numbers. The decline caused by succession was relatively slow, but the gravity of this threat is increased by the fact that it is widespread and affects virtually all meadows in the region. All concerned conservation efforts should primarily be aimed at halting ill-advised afforestation of meadow habitats in urban landscapes. This would require changing the paradigm according to which afforestation is often perceived as an optimal remedy for various environmental problems in urban landscapes, including biodiversity crisis.